Growth curve analysis of Garut sheep and its crossbreds - Inounu, Ismeth; Mauluddin, D; Noor, R.R; ., Subandriyo (Indonesian Journal of Animal and Veterinary Sciences, 2007)
Data of body weight of Garut sheep and its crossbreds of 488 head, consist ofÂ  149 head of Garut sheep, 115 head of St. Croix X Garut (HG), 68 head of Mouton Charollais X Garut (MG), 101 head of MG X HG (MHG) and 55 head of HG X MG (HMG) which is collected from Indonesian Research Institute for Animal Production at Bogor station were used in individual growth curve analysis. Three growth curve non linier model were used in this study i.e Logistik, Gompertz and Von Bertalanffy models. Comparisons were made among these models for goodness of fit, biological interpretability of parameters and computional ease and effect of genotype and environment in them. Least square means growth curve parameters which have biological interpretability were used to compare effect the genotype, interse mated procces and estimated heterosis effect. The result indicated that Von Bertalanffy was the best model in fitting the data from Garut and Crossbreds although the model needed more iteration than others in computations. All models have good biological interpretability especially for parameter mature size (A) and rate of maturity (k). Genotype, year of birth, sex and type of birth reared were important effects (p<0.01) in mature size (A) for all models except effect of type of birth rearing (P<0.05) in Logistic model. Year of birth had important effect (p<0.01) in rate of maturity (k) for all models. Genotype, year of birth, sex, parity and type of birth reared also had important effect (p<0.01) in parameter b/M; except b parameter in Von Bertalanffy was affected significantly by sex (P<0.05). Key Words: Growth Curve, Garut Sheep and Crossbreds, Relative Superiority